Incumbents as disruptor and their disruptive behaviour enabling disruptive innovation: case study of high performance and low cost CPU and foundry market. Issue 12 (2nd December 2018) - Park, Changhyun
ABSTRACT: The ability and role of incumbents to enable and sustain disruptive innovation is underestimated so far, compared with new entrants. Thus, this research aimed to observe incumbents' role as a disruptor and their disruptive behaviours to enable disruptive innovation in different market segments. Based on two case studies of CPU and foundry markets, it was observed that incumbents enabled disruptive innovation by adjusting disruptive window in the context of performance trajectories and discontinuous time, and they sustained their market leadership by having advantages through continuous cost reduction and accumulated technological knowledge in high performance and low cost market. This study has extended the theory of disruptive innovation by including incumbents' role and their disruptive behaviours and has practical implications as well for incumbents and new entrants to establish competitive technology strategy at the organisation as well as national level.